Chemical Constituents of the Methanolic Extract of Leaves of Leiothrix spiralis Ruhland and Their Antimicrobial Activity - de Freitas Araujo, Marcelo Gonzaga [UNESP]; Hilario, Felipe [UNESP]; Nogueira, Leonardo Gorla [UNESP]; Vilegas, Wagner [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Bauab, Tais Maria [UNESP] (Mdpi Ag, 2011)
Chemical fractionation of the methanolic extract of leaves of Leiothrix spiralis Ruhland afforded the flavonoids luteolin- 6- C-beta-D-glucopyranoside (1), 7-methoxyluteolin-6-C-beta-D-glucopyranoside (2), 7-methoxyluteolin-8-C-beta-D-glucopyranoside (3), 4'-methoxyluteolin-6-C-beta-D-glucopyranoside (4), and 6- hydroxy-7-methoxyluteolin (5), and the xanthones 8-carboxymethyl-1,5,6-trihydroxy-3-methoxyxanthone (6), 8-carboxymethyl-1,3,5,6- tetrahydroxyxanthone (7). Methanolic extract, fractions, and isolated compounds of the leaves of L. spiralis were assayed against Gram-positive (Staphylococcus aureus, Bacillus subtilis and Enterococcus faecalis) and Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Salmonella setubal and Helicobacter pylori) and fungi (the yeasts Candida albicans, C. tropicalis, C. krusei and C. parapsilosis). We observed the best minimum inhibitory concentration values for the methanolic extract against Candida parapsilosis, for the fraction 5 + 6 against Gram-negative bacteria E. coli and P. aeruginosa, and compound 7 against all tested Candida strains. The methanolic extract contents suggest that this species may be a promising source of compounds to produce natural phytomedicines.
Keywords: Eriocaulaceae; Leiothrix spiralis; phenolic compounds; antimicrobial activity